The shape of the orbit in FLRW spacetimes. (5th November 2018) - Garfinkle, David; Mead, Lawrence R; Ringermacher, H I
Abstract: The shape of the orbit of a free particle is examined in Friedmann-Lemaître-Robertson-Walker (FLRW) cosmologies. The spatial projection of the orbit is time-independent and has a simple geometric description. We relate this description to the expression in terms of standard FLRW coordinates.